GW24-e3018 Long-term Medication Adherence Following Acute Coronary Syndrome in Patients with and without Recurrent Cardiovascular Events: Analysis of the HealthCore Integrated Research Database 2006–2011. (1st October 2013) - S Reddy, Vanessa; Luthra, Rakesh; Xu, Yaping; Fisher, Maxine; Power, Thomas; Wilhelm, Ken; Cziraky, Mark
Abstract : Objectives: Medication adherence is critical for the management of chronic disorders such as cardiovascular disease. However, long-term adherence has not been well described in acute coronary syndrome patients. The aim of this study is to assess long-term medication adherence to guideline-recommended treatments following acute coronary syndrome in patients with and without recurrent cardiovascular events. Methods: Acute coronary syndrome patients hospitalised with an ICD-9 code for acute myocardial infarction or unstable angina were identified from the HealthCore Integrated Research Database (HIRD SM ) between January 2006 and September 2011. Mean medication possession ratios for guideline-recommended acute coronary syndrome treatments were assessed 1 and 3 years after the index acute coronary syndrome using pharmacy claims data, stratified by presence or absence of recurrent cardiovascular events, defined as stroke, myocardial infarction or coronary heart disease-related mortality. Results: Of the 140, 903 acute coronary syndrome patients identified, 22% had > 1 recurrent cardiovascular event and were on average older (72.4 versus 65.2 years), included more women (44.5 versus 40.6%), and had more comorbidities (e.g. diabetes mellitus 49.7 versus 39.7%) as compared to those without recurrent events. After 3 years, patients were most adherent to antihypertensives (medication possession ratio = 0.70). The medication possession ratio ranged from 0.53 to 0.70 among different guideline-recommended treatments for patients with acute coronary syndrome. Overall, differences in medication possession ratios in patients with versus without recurrent events were small, although some were statistically significant. Conclusions: At 3 years, medication adherence was highest to antihypertensives. The gaps in adherence highlight the need to encourage and monitor treatment use following acute coronary syndrome, as well as understand class-specific adherence barriers, to improve long-term outcomes.